USING MISCUE ANALYSIS OF STUDENTS’ ORAL READING PROCESS: THE CASE OF TAIWANESE ELEMENTARY STUDENTS - Saragih, Esteria Hernauli Br; Huei-Hsuan, Lin (Kairos English Language Teaching Journal, 2022)
This study is aimed to analyze the oral reading process of two Taiwanese elementary students. Particularly it focuses on students’ miscues in reading the text. According to Goodman (1973) the he reading miscue refers to the symptoms when a reader diverges from the assigned text. Analyzing reading miscues is significant since it reveals how a reader acquires comprehensions through reading process. Therefore, educators should not treat reading miscues simply as mistakes and dismiss them accordingly. Two Taiwanese elementary students in the fifth grade were observed in this study: One was a proficient English reader, while another was considered a struggling reader. Not only were they asked to read the text, they were engaged unaided retelling of the story afterwards. From their retellings of the story, it was evident that both students understood the story well. But the proficient reader was able to retell in English, while the other could retell the story in Chinese. Through the miscue analysis of their readings, we were able to see that the proficient reader used the strategies of confirming, omission and substitution in reading, while the struggling reader stumbled quite often, inserted words into the text and used substitutes also. Though it appeared that proficient reader did much better than the struggling reader. But based on the miscue analysis, the struggling reader was making effort to engage the text, and the diversion from the text did not hinder his comprehension of the text, but he was just not able to recount the story in English. Miscue analysis in this case served as a useful tool for teachers to map out students’ reading process to differentiate how ways of diversions from the text influenced students’ engagement with the text. In doing so, English teachers are able to better assess students English capacities in a more detailed manner by addressing to their personal conditions